Pengaruh Iklim Komunikasi Organisasi Terhadap Motivasi Kerja Karyawan - Nashria, Novita; Halilah, Ii (Jurnal Riset Bisnis dan Investasi, 2015)
The purpose of this paper is to determine organizational communication climate, employee motivation and impact of organizational communication climate to employee motivation in PT Bank Tabungan Negara (Persero) Tbk. Bandung Branch Office. A communication climate is perceptions of communication events, human behavior, the response of employees to other employees, expectations, interpersonal conflicts and opportunities for growth within the organization. Based on the theory, communication within the organization also has four main functions one of them is motivation. This research uses/employs descriptive analysis method, classic assumption test, regression test, correlation and hypothesis test in analyzing the data obtained through the observation, interviews, literature study and questionnaire. From the simple linear regression test results, obtained is the equation Y = 38.322 + 0.722X with the results of R-Square in the amount of 0.282; meaning that organizational communication climate variable can give impact 28.2% on employee motivation.